Generalised Presic Type Operators in Modular Metric Space and an Application to Integral Equations of Caratheodory Type Functions. (7th October 2021) - Alshammari, Fahad Sameer; Reshma, K. P.; R., Rajagopalan; George, Reny
Abstract : Extending the Presic type operators to modular spaces, we introduce generalised Presic type w -contractive mappings and strongly w -contractive mappings in a modular metric space and establish fixed-point theorems for such contractions in modular spaces. Ulam–Hyers stability of the fixed-point equation involving Presic type operators is also discussed. Our results extend and generalise some known results in the literature. The results are supported by appropriate example and an application to Caratheodory type integral equation.